Mimicking Bollywood in Slumdog Millionaire: Global Hollywood's Newest Co-Optation of Culture. (January 2014) - Cox, Nicole B.; Proffitt, Jennifer M.
In an age when mass media transcend geographic barriers, Slumdog Millionaire ( SDM ) represents a new type of film in the global media market—a seemingly Bollywood, although not technically Bollywood, production. As film-going provides a site for ideological and cultural production, this article examines SDM 's success as a product imitative of Bollywood film. Due to its recency, SDM has yet to be examined as a product that crosses both cultural and geographic boundaries with commercial ties to major Hollywood media conglomerates. Applying political economic theory, this research examines the reasons for Hollywood involvement in a film production that is mimetic of the Bollywood genre, in an attempt to better understand the global political economic factors that drive the film industry today.